Centralized Information Web-oriented the Educational Environment of Ukraine - Shapovalov, Viktor; Shapovalov, Yevhenii; Bilyk, Zhanna; Tarasenko, Roman; Atamas, Artem; Tron, Vitaliy.V. (My University, 2019)
The modern development of science and technology has provided high quantity of information. This information must be systemized and classified. For taxonomization of educational materials, it was proposed to use existing graph- generators and graph-visualizers of the TODOS IT platform. A separate aspect of the TODOS IT platform is the possibility of using a centralized web-oriented learning environment. Creation of the system and transdisciplinary knowledge is a problem of modern education, which can be solved by creating a centralized web-oriented educational environment. Using this approach is an important part of the learning process. Such a centralized web-oriented environment based on the ontological approach involves filling, adaptive educational services with information resources that reflect the conceptual system of a particular discipline. One of the systems providing not only collection of information but include its systemizing is centralized web-oriented educational environment based on Ontology4 system. Ontology 4 use elements of the TODOS. The paper presents specific developments of one centralized web-oriented educational environment can be used to teach different subjects such as biology, chemistry, Ukrainian language and literature, using the STEM approach.
Keywords: кафедра харчової хімії; unified network-centric educational information; уніфікована мережева освітня інформація; systematics of microorganisms; систематика мікроорганізмів; Ontology4; multiagent system; багатоагентна система